Biopolymers for food design - Grumezescu, Alexandru Mihai; Holban, Alina Maria (Academic Press, an imprint of Elsevier, 2018)
'Biopolymers for Food Design, ' Volume 20 in the Handbook of Bioengineering series, describes how biopolymers have made a major impact in the food industry, from food design, to food control and safety. Biopolymers can be used in the development of novel nutritional alternatives, to replace difficult to obtain food products, or for foods inaccessible or inappropriate for a particular population (i.e. allergic to specific components). In addition, some polymers can be used as functional ingredients, and can also represent efficient scaffolds for food ingredients with therapeutic values. This valuable reference is ideal for those looking for new solutions for the food industry. -- Provided by publisher.
Includes index.
Keywords: Artificial foods.; Food substitutes.; Biopolymers.; elektronické knihy; electronic books